An investigation into the effects of metformin in combination with Clofarabine for the treatment of leukaemia using T-lymphoblastic leukaemia cell lines - Nemuvumoni, Ntakadzeni (My University, 2020)
T-cell acute lymphoblastic leukaemia (T-ALL) is an aggressive cancer that develops from the expression of a high number of immature progenitors that encode T-cell development. T-ALL is a significant contributor to mortality in children and adults, and accounts for 15% of paediatric acute lymphoblastic leukaemia (ALL) and 25% of adult ALL cases. Clofarabine is a chemotherapeutic drug used to treat multiple leukaemia including T-ALL. Cellular metabolic alterations can result in resistance to clofarabine treatment. Advanced chemotherapeutic strategies are required to improve clofarabine activity. Metformin, an antidiabetic drug, is of interest for novel drug combination therapy with clofarabine as it can enhance metabolic processes required in enhancing clofarabine effectiveness. Our results by XTT assay indicated that metformin alone significantly inhibited cell proliferation by 17-82% in CEM and by 20-51% in THP1 cells. The presence of metformin seems to enhance the sensitivity of CEM cells to clofarabine but induced slight resistance to clofarabine in THP1. Using Western blotting we looked at the expression of nucleoside metabolism enzymes. In CEM cells, in comparison to untreated control, metformin-treated cells showed decreased expression of thymidine kinase (TK-1) to 85±3% and 40±5% in 5mM treatment at 48 and 72 hours exposure, respectively. Thymidylate synthase (TS) levels were also decreased to 73±5% and 56±45 in 5mM treatment at 48 and 72 hours exposure, respectively, in comparison to untreated controls. There was no statistically significant change in TK-1 expression in THP1 cells. As clofarabine depends on deoxycytidine kinase (dCK)and deoxyguanosine kinase (dGK) for its effectiveness, we investigated the effect of metformin on expression levels of dCK and dGK. We found a change in expression levels of dCK and dGKwith 5mM metformin at 72 hours which caused a 69% (31±1%) and 56% (44±10%) reduction in CEM cells. In THP1 cells we found an increase of 22% (78±5%) in dCK with 2.5mM metformin at 24 hours treatment. Apoptosis with both metformin and metformin/clofarabine treatment was not evident, either through caspase-3 cleavage or DNA fragmentation in CEM and THP1 cell lines. In conclusion, metformin enhances clofarabine effectiveness in ALL CEM but slightly induces clofarabine resistance in AML THP1 cells
A dissertation submitted in fulfilment of the requirements for the degree Masters of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, 2020
Keywords: Lymphocytes; Leukemia